Evaluation of the Oral Health Education for Nurses and Community Health Workers (Project OHE-NCHeW) in Nigeria - Abimbola M. Oladayo; Folake B. Lawal; Oyinkansola O. Sofola; Omolara G. Uti; Afolabi Oyapero; Adetayo Aborisade; Mojisola Olujitan; Omotayo F. Fagbule; Adeola T. Williams; Aderonke Dedeke; Ejiro Idiga; Yahya-Imam Abdul-Kabir Adegoke; et al. (International Dental Journal, 2025)
Introduction: Educating primary healthcare workers (PHCWs) on oral health and its association with systemic health, as well as equipping them with skills to identify common oral diseases for referral to the dentist, is crucial for improving overall health outcomes in underserved regions. However, traditional oral health education programs for PHCWs have yet to increase patient referrals to dental centers significantly, hence the need for competency-based oral health training. This study evaluated the effectiveness of a competency-based oral health training pilot program – Project OHE-NCHeW on the oral health knowledge and referral practices of nurses and community health workers (CHWs) in Nigeria. Methods: We utilized a quasi-experimental design with pre-and post-test assessments. One hundred twenty nurses and CHWs (60 intervention, 60 control) across Lagos, Kano, and Ibadan were recruited via cluster sampling. The intervention group underwent a 5-day competency-based oral health training, while the control group received a single-session lecture. Evaluations were conducted immediately after training and 3 months later to assess knowledge, attitudes, and referral practices (KAP) using a validated questionnaire. Results: Overall, the mean age of the participants was 41.4 ± 10.3 years, with an average of 15.3 ± 9.8 years of practice. Both groups had similar baseline KAP scores. Post-training, the intervention group showed significant improvements in oral health knowledge (P < .0001) and practice scores (P = .0096) only. Referral outcomes varied by location, with Kano logging the highest number of referrals (60.0%), and many (57.5%) of the referred patients attended the clinic (57.5%). Decayed teeth (44.1%) and gum diseases (30.8%) were the most common reasons for referral across all sites. Conclusion: The pilot training significantly enhanced the PHCW's oral knowledge and referral practices, demonstrating the potential to strengthen primary care and inform policies aimed at integrating oral health into primary care frameworks for broader public health impact.